Smart Molecular Recognition: From Key-to-Lock Principle to Memory-Based Selectivity - Gatiatulin, Askar K.; Ziganshin, Marat A.; Gorbatchuk, Valery V. (Frontiers in Chemistry, 2020)
The formation and decomposition of inclusion compounds with a solid-solid phase transition may be very selective to the guest molecular structure. This selectivity may function in essentially different ways than defined by the classical concept of molecular recognition, which implies the preferential binding of complementary molecules. Solid inclusion compounds may take part as an initial or/and final state in several processes of different types summarized in this review, which selectivity is boosted by cooperativity of participating molecular crystals. Some of these processes resemble switching electronic devices and can be called smart giving practically absolute molecular recognition.